Análisis De La Fuerza Explosiva En El Golpe De Balón Con El Pie En Los Futbolistas Categoría Senior De La Universidad Nacional De Chimborazo – Ecuador. Estudio De Caso: Test De Salto Horizontal - Moreno, Orlando David Mazón; Vite, Grace Amparo Obregón; Ruiz, Marcos Vinicio Caiza; Machado, Juan Carlos Bayas; Machado, Ramón Fernando Bayas (European Scientific Journal, ESJ, 2017)
The objetive of this study is to research the incidence of explosive strength on the ball kick of senior category soccer players from the “Universidad Nacional de Chimborazo”. The study was carried out through the application of a comprehensive training program to improve explosive strength and ball kick for 8 weeks. In this study, 50 soccer players were also evaluated. The age, body weight (kg), height (cm), and body mass index were also evaluated. The pre – post ball kick horizontal jump test was applied as well. The soccer sketch 2.5.0 program was used for the preparation of the training sessions, while the SPSS statistical package was used for the results tabulation. The results obtained are as follows: average age of 21.82, average body mass index 26.72 (kg/m2 ). An average of 2.13cm was obtained in the pre-test horizontal jump while an average of 2.16 cm was obtained in the post-test whit a level of significance of 0.002. In conclusion, the application of training sessions based on comprehensive exercises of explosive strength and ball kick are very important in improving the sports performance of the soccer players.